1996
DOI: 10.1002/pro.5560050801
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding in the endoplasmic reticulum: Lessons from the human chorionic gonadotropin β subunit

Abstract: There have been few studies of protein folding in the endoplasmic reticulum of intact mammalian cells. In the one case where the in vivo and in vitro folding pathways of a mammalian secretory protein have been compared, the folding of the human chorionic gonadotropin b subunit (hCG-b), the order of formation of the detected folding intermediates is the same. The rate and efficiency with which multidomain proteins such as hCG-P fold to native structure in intact cells is higher than in vitro, although intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 73 publications
2
46
0
Order By: Relevance
“…This result is consistent with the model of hCG assembly proposed by Ruddon et al (17) and shows that the conformation of the seatbelt is not restricted to the position it occupies in hCG (2, 3). These data also support a prediction TABLE IV Binding of selected analogs in alternate sandwich assays Analogs were captured with A113, an antibody to the ␣-subunit, and detected with radiolabeled antibodies to the ␤-subunit.…”
Section: Implications Of These Observations For Hcg Assembly In the Esupporting
confidence: 93%
See 1 more Smart Citation
“…This result is consistent with the model of hCG assembly proposed by Ruddon et al (17) and shows that the conformation of the seatbelt is not restricted to the position it occupies in hCG (2, 3). These data also support a prediction TABLE IV Binding of selected analogs in alternate sandwich assays Analogs were captured with A113, an antibody to the ␣-subunit, and detected with radiolabeled antibodies to the ␤-subunit.…”
Section: Implications Of These Observations For Hcg Assembly In the Esupporting
confidence: 93%
“…This suggests that the amino-terminal half of the seatbelt is not as mobile as the carboxyl-terminal half or that the amino-terminal half of the seatbelt contributes to interactions between the subunits needed for docking when the seatbelt is not latched. This observation is also consistent with the proposal that the small seatbelt loop is formed prior to docking of the subunits (17).…”
Section: Implications Of These Observations For Hcg Assembly In the Esupporting
confidence: 92%
“…The C terminus of the seatbelt is "latched" by a disulfide bond to a cysteine in loop 1 of the ␤-subunit. Earlier studies suggested that heterodimer assembly occurred by a "wraparound" mechanism in which the seatbelt became latched after the subunits docked (3). Contrary to these studies, we reported that the assembly of human choriogonadotropin (hCG), human follitropin (hFSH), and human thyrotropin (hTSH) occurred in the endoplasmic reticulum only after the seatbelt was latched (4,5).…”
mentioning
confidence: 73%
“…On the other hand some diseases are due to the synthesis of a mutant or misfolded protein, which gets a novel activity (such as the tendency to from aggregates) with pathological characteristics. Different human diseases, which involve protein misfolding have been studied [60,61] .…”
Section: Molecular Chaperonesmentioning
confidence: 99%